2019
DOI: 10.1016/j.lungcan.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective response analysis of BAP1 expression to predict the clinical activity of systemic cytotoxic chemotherapy in mesothelioma

Abstract: Introduction: BRCA1 associated protein-1 (BAP1) is a key tumor driver in mesothelioma and a potential biomarker predicting response to several targeted therapies in clinical testing. Whether it also modulates response to cytotoxic chemotherapy is undetermined. This study used retrospective response analysis of BAP1 expression in archival tumor biopsies taken from patients in the MS01 trial (NCT00075699). We aimed to determine if BAP1 expression correlated with overall survival within the three treatment arms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…This correlation was further supported by immunohistochemistry in primary mesothelioma tissue samples collected as part of the MSO1 clinical trial (NCT00075699) (37). MPM tissue samples that lacked nuclear BAP1 did show elevated levels of DR4 and DR5 ( Supplementary Fig.…”
Section: Loss Of Bap1 Activity Correlates With Increased Dr4 and Dr5 mentioning
confidence: 61%
See 1 more Smart Citation
“…This correlation was further supported by immunohistochemistry in primary mesothelioma tissue samples collected as part of the MSO1 clinical trial (NCT00075699) (37). MPM tissue samples that lacked nuclear BAP1 did show elevated levels of DR4 and DR5 ( Supplementary Fig.…”
Section: Loss Of Bap1 Activity Correlates With Increased Dr4 and Dr5 mentioning
confidence: 61%
“…were stored as formalin fixed paraffin embedded (FFPE) blocks or as unstained mounted sections as previously described (37) ; medium staining=2; strong staining=3).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…RT is used as an adjuvant or neoadjuvant treatment in MPM, mainly in a palliative setting (8)(9)(10). As standard practice, patients undergoing an EPP receive adjuvant conventionally fractionated RT (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) in the ipsilateral hemithorax area (18,19). In node-negative MPM patients, neoadjuvant therapy, based on intensity-modulated RT (IMRT) consisting of a fractionated irradiation of 5-6 Gy, is delivered before EPP (20)(21)(22).…”
Section: Radiotherapymentioning
confidence: 99%
“…Genomic studies on MPM cells reported a reduced or absent expression of an enzyme involved in DNA repair and Ca 2+ -dependent apoptosis BAP1 in ∼50% of sporadic MPMs. In vitro studies demonstrated that BAP1-mutated cells are less sensitive to ionizing radiation causing DNA doublestrand breaks (50,51) or to the DNA synthesis inhibitor gemcitabine (52), highlighting the contribution of BAP1 in DNA damage signaling and repair and a possible role as a predictive biomarker (53). Inherited loss-of-function mutations in BAP1 predispose to multiple carcinomas, including mesothelioma (54)(55)(56).…”
Section: Synthetic Lethal Therapiesmentioning
confidence: 99%
“…Recently, BAP1 status has been associated with drug response [28,29]. In vitro studies showed MPM cell lines carrying BAP1 mutations were significantly less sensitive to gemcitabine compared to wild-type cells.…”
Section: Bap1mentioning
confidence: 99%